Human pulp responses to in-office tooth bleaching - de Souza Costa, Carlos Alberto [UNESP]; Riehl, Heraldo; Kina, Joao Fernando [UNESP]; Sacono, Nancy Tomoko [UNESP]; Hebling, Josimeri [UNESP] (Mosby-elsevier, 2010)
Objective. To evaluate and compare the responses of human incisor and premolar pulps after bleaching.Study design. A bleaching agent with 38% hydrogen peroxide (H(2)O(2)) was applied on the buccal surface of 10 sound lower teeth (G1: 6 premolars; G2: 4 incisors) for 45 minutes. Three premolars and 3 incisors that received only rubber/pumice prophylaxis were used as control groups G3 and G4, respectively. Two days after the bleaching procedure, the teeth were extracted and processed for histologic evaluation.Results. Only in G2 (4 incisors) were any changes in the pulp detected. In the coronal pulp there was a large zone of coagulation necrosis. The radicular pulp showed mild inflammatory changes manifested as an accumulation of mononuclear cells around congested and dilated blood vessels. No pulpal damage was seen in either of the control groups (G3 and G4) or in group G1.Conclusion. Bleaching with 38% H(2)O(2) for 45 minutes causes irreversible pulp damage in lower incisors but not in premolars. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2010; 109: e59-e64)